DO HUMAN DEVELOPMENT INDEX (HDI) AND UNEMPLOYMENT AFFECT POVERTY IN MADURA, INDONESIA? - Kamalia, Putri Ulfa; Subroto, Waspodo Tjipto; Sakti, Norida Canda (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The main objective of this study is to analyze the effect of Human Development Index (HDI) and unemployment rate on poverty in Madura. This research uses a quantitative approach with associative research type. The sample in this study includes HDI which is measured based on the HDI level, unemployment which is measured based on the open unemployment rate and poverty which is measured based on the poverty rate of four districts in Madura for the last 10 years starting from 2014-2023. Based on the results of the research conducted, it can be concluded that the Human Development Index affects poverty in Madura. Meanwhile, unemployment has no effect on poverty in Madura. However, both variables, namely the Human Development Index and unemployment simultaneously affect poverty in Madura by 51.55%.